2020
DOI: 10.1155/2020/2936838
|View full text |Cite
|
Sign up to set email alerts
|

Levitation Stability and Hopf Bifurcation of EMS Maglev Trains

Abstract: This paper analyzed the mechanical characteristics of single electromagnet system and elastic track beam of EMS maglev train and established a five-dimensional dynamics model of single electromagnet-track beam coupled system with classical PD control strategy adopted for its levitation system. Then, based on the Hurwitz criterion and the high-dimensional Hopf bifurcation theory, the stability of the coupled system is analyzed; the existence of the Hopf bifurcation is discussed and the bifurcation direction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In the previous formula, X 0 � x 0 y 0 􏼂 􏼃 T 􏼐 􏼑 and ΔX � Δx Δy 􏼂 􏼃 T 􏼐 􏼑. Substituting equation (12) into equation (11), using Taylor expansion and ignoring the higher-order small quantities in it, we get…”
Section: Vehicle-rail Coupling Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous formula, X 0 � x 0 y 0 􏼂 􏼃 T 􏼐 􏼑 and ΔX � Δx Δy 􏼂 􏼃 T 􏼐 􏼑. Substituting equation (12) into equation (11), using Taylor expansion and ignoring the higher-order small quantities in it, we get…”
Section: Vehicle-rail Coupling Modelmentioning
confidence: 99%
“…At present, the suspension control model of the maglev train mostly adopts the single electromagnet suspension system model, and the linearized model is applied to the classical control theory-PID or PD controller for control. In the suspension control of the maglev train, it is divided into voltage [12,13] and current [14][15][16][17][18] as the control target.…”
Section: Introductionmentioning
confidence: 99%
“…2,14 To determine the dynamic stability of a maglev system, Zhou et al 15 used the Lyapunov characteristic index, and some researchers used the Hopf bifurcation. 1618…”
Section: Introductionmentioning
confidence: 99%
“…2,14 To determine the dynamic stability of a maglev system, Zhou et al 15 used the Lyapunov characteristic index, and some researchers used the Hopf bifurcation. [16][17][18] German Transrapid maglevs, Japanese L0 maglevs and the first commercial high-speed maglev based on the German Transrapid technology in Shanghai have shown that the speed of future guideway vehicles can reach 600 km/h or higher. Therefore, there is an urgent requirement for the development of more capable braking methods.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the merits of wide speed range, low noise and low maintenance cost, the maglev train is a very competitive green ground transportation tool [2,3]. Based on the levitation principle, the maglev technologies can be divided into four forms: permanent magnetic suspension (PMS) [4,5], electromagnetic suspension (EMS) [6,7], electrodynamic suspension (EDS) [8,9] and flux pining suspension (FPS) [10,11]. Among them, the electrodynamic suspension is further divided into permanent magnet electrodynamic suspension (PM EDS) and superconducting electrodynamic suspension (SC EDS).…”
Section: Introductionmentioning
confidence: 99%